Agro-processing and horticultural exports from Africa - Fukase, Emiko; Martin, Will (International Food Policy Research Institute, 2017)
This paper analyzes the principal features of agro-processing and horticultural exports from SSA and explores policy alternatives based on simulation analyses. We first provide a conceptual section focusing on changing patterns of processing and exports (section 2). We then examine how the pattern of exports from Africa compares with the pattern in other regions (section 3). Following that, we examine the directions of trade in African agricultural exports and the patterns of protection facing, and imposed by, African countries (section 4). Next, we turn to simulation exercises to examine the impacts of potential reforms on exports of processed and horticultural exports from Africa (section 5). With this as background, we turn to consider the options for policy makers in Africa (section 6).